Lord Loss - Shan, Darren (London : HarperCollins, 2005)
Presumably the only witness to the horrific and bloody murder of his entire family, a teenage boy must outwit not only the mental health professionals determined to cure his delusion, but also the demonic forces only he can see.
Keywords: Demonology -- Fiction; Horror stories